Ibn Tufayl and the problem of intellectual and religious pluralism - عجيني زاهر; حامد ابراهيم (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research discussed the attitude of Ibn Tufayl of religion in general, and of religious pluralism in particular, it was therefore necessary to address the nature of religious knowledge with him and the forms of access to it, all through his famous story "Hayy Ibn Yaqzan" in which Ibn Tufail showed forms, plurality and methods of this knowledge. That is why we dealt with the concept of religious pluralism idiomatically and linguistically, that is, how it was defined in Western and Arabic philosophical dictionaries and literature. Then, the research discussed the role of pluralism in Ibn Tufail’s thoughts, and the aim was to reach a discussion of the concept of salvation in Ibn Tufail’s philosophy, which we can find in all forms of religiosity and methods to reach this salvation.